HUBUNGAN PENGETAHUAN DAN SIKAP MASYARAKAT KECAMATAN CAKUNG JAKARTA TIMUR TERHADAP PENGGUNAAN DAN RESISTENSI ANTIBIOTIK - Rusdi, Numlil Khaira; Hastuti, Septianita Hastuti; Maifitrianti, Maifitrianti; Nurhasnah, Nurhasnah; Azizah, Rahma Nur (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2024)
Antibiotic resistance is one of the serious problems that are being faced today. Low levels of knowledge and poor public attitudes about antibiotic use can trigger resistance. This study aims to determine the level of knowledge, attitudes, and relationships between the level of knowledge and attitudes of the community about antibiotic use and resistance in Cakung District, East Jakarta for the July-August 2023 period. The design of this study was descriptive with cross sectional method. The sampling technique uses purposive sampling. The source of data in this study is primary data in the form of knowledge questionnaires and attitudes about antibiotics. Knowledge is categorized with high and low, while attitude is categorized with positive and negative. The results showed that as many as 400 respondents met the inclusion and exclusion criteria. The characteristics of public knowledge about antibiotics showed that 65.3% of respondents had high knowledge and 34.7% had low knowledge. As many as 61.0% of respondents had a positive attitude and 39% had a negative attitude towards the use of antibiotics and resistance. The results of the bivariate analysis showed that there was a significant relationship between the level of knowledge and people's attitudes towards antibiotic use and resistance (P<0.000). The higher the level of knowledge of the community, the more positive the attitude of the community towards the wise use of antibiotics.